Evaluasi Terhadap Penggunaan Aspal Buton sebagai Bahan Tambah Terhadap Karakteristik dan Parameter Campuran Beraspal Modifikasi - Muhammad Karami (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
The aim of the research was to see the effect of the utilization of Buton asphalt as subtitution in part os cement asphalt and fine aggregate on the characteristics and parameters of asphalt mixture. There were seven characteristics and parameters which requirements should be fulfiled in order that a an asphalt mixture could be made which were stability, fatique, Marshall quotient, air pores or voids in mixtures (VIM), pores within aggregates or voids in mineral aggregates (VMA), air pores filled with asphalt or void filled with asphalt (VFA) and VIM in the condition of absolut density or percentage refusal density (VIM-PRD). A hard asphalt of 60/70 penetration of a Pertamina product and aggregates from Batu Makmur stone crusher, Lampung Selatan were used in the research. The Buton asphalt used was in original form from its deposit without any special treatment in advance and was containing 32 % asphalt and 68 % minerals. Graded density of wearing asphalted mixture or asphalt concrete wearing course (AC-WC) with total asphalt content of 4.5 7.0 % divided into 3.0 % hard asphalt and the rest was Buton asphalt. The result indicated that material proportion could be used in the asphalted mixture complied to all characteristics and AC-WC parameters was 3 % hard asphalt, 88.2 90.7 % aggregate (crushed stones), and 6.3 8.8 % Buton asphalt.